The prevalence of dementia in a Portuguese community sample: a 10/66 Dementia Research Group study - Gonçalves-Pereira, Manuel (2017)
This study was supported by a research grant from FCT - Fundacao para a Ciencia e a Tecnologia, the Portuguese national funding agency for science, research and technology (Project reference PTDC/SAU-EPI/113652/2009: "Prevalence of old age neuropsychiatric disorders: contribution to mental health policy in Portugal"; PI: Miguel Xavier). A. Matthew Prina was supported by the MRC (MR/K021907/1). iNOVA4Health - UID/Multi/04462/2013, a program financially supported by Fundacao para a Ciencia e Tecnologia / Ministerio da Educacao e Ciencia, through national funds and co-funded by FEDER under the PT2020 Partnership Agreement is acknowledged.